Studi tekno-ekonomi pemurnian biogas dari limbah domestik - Akhwari Wahyu P; Moh Fahrurrozi; Muslikhin Hidayat (Jurnal Rekayasa Proses, 2012)
Biogas purification can increase the caloric value of combustion and prevent corrosion. Biogas with 95% of methane is similar to pipeline quality natural gas. The objective of this research was to study technical and economical feasibility of biogas purification and also to estimate gas production cost and scale up capacities.This research used the secondary data from pilot plant of Biogas of Pasar Induk Buah dan Sayuran Gemah Ripah, Gamping, Sleman, Yogyakarta. This research was to obtain the production cost and scale up capacities for each biogas purification method. The sensitivity analysis was conducted to study the influence of gas composition ranged at 30-70% CH4 toward the flow of absorbent to gas ratio, the price of waste changed from decreasing 100% up to increasing 100% and the finance changed ranged at 0-15% to the change of production cost.The result showed that water scrubber was the cheapest method for scrubbing impurities. The production cost of scale up capacities compared to the price of pipeline quality natural gas which ranged at 6-10 US$/MMBtu. The minimum capacity of economical biogas purification methods was 100 tons waste/day. The influence of gas composition ranged at 30-70% of CH4 produced the L/G value change in the absorber column ranged at 0,005-0,025; the influence of waste price from decreasing and up to increasing 100% and finances from 0-15% produced the production cost change ranged at 3-8 US$/MMBtu and 2-14 US$/MMBtu respectively.